Cellular uptake of PLA nanoparticles studied by light and electron microscopy: synthesis, characterization and biocompatibility studies using an iridium(iii) complex as correlative label. Issue 23 (29th February 2016) - Reifarth, Martin; Pretzel, David; Schubert, Stephanie; Weber, Christine; Heintzmann, Rainer; Hoeppener, Stephanie; Schubert, Ulrich S.
Abstract : We present the synthesis of polylactide by ring-opening polymerization using a luminescent iridium(iii ) complex acting as initiator. Abstract : We present the synthesis of polylactide by ring-opening polymerization using a luminescent iridium(iii ) complex acting as initiator. The polymer was formulated into nanoparticles, which were taken up by HEK-293 cells. We could show that the particles provided an appropriate contrast in both superresolution fluorescence and electron microscopy, and, moreover, are non-toxic, in contrast to the free iridium complex.